(427) L'impot d'education -proposition a commenter ضريبة التعليم - اقتراح للتعليق - El-Sayed, Atef (INP, 2024)
This study addresses the concept of an "Education Tax" as a fiscal instrument that can be utilized to support economic and social development within the framework of the evolving functions of taxation systems. Traditionally, taxation was viewed merely as a mechanism for generating public revenues for the state treasury without direct economic objectives. However, in modern economic thought, taxation has increasingly become an effective tool through which governments can influence economic activities and guide development processes. Based on this perspective, the study proposes an educational tax framework intended to address several economic and social challenges associated with development, particularly in developing countries. The research adopted an analytical approach focusing on the economic role of taxation policies and their capacity to influence individual behavior and economic activities. It examined the effectiveness and limitations of fiscal instruments through an analysis of the relationship between tax burdens and taxpayers' responses while considering economic, psychological, and social determinants affecting individuals’ reactions toward taxation systems. The study emphasized that the economic impact of taxation depends not only on the magnitude of the financial burden imposed but also on broader psychological, historical, and social factors that shape public acceptance of taxation. Furthermore, the study demonstrates that the effectiveness of tax policy depends significantly on individuals’ willingness to contribute to public obligations. Excessive taxation may generate undesirable outcomes such as tax evasion and inefficient allocation of human and economic resources. Consequently, the research stresses the importance of establishing an optimal level of taxation that achieves development objectives while preserving economic and social stability. The findings suggest that the proposed education tax may serve as an effective mechanism for financing education and strengthening human capital development, provided that it is designed according to balanced economic and social principles that reflect the characteristics and conditions of the society in which it is implemented.